2014
DOI: 10.1117/12.2054261
|View full text |Cite
|
Sign up to set email alerts
|

Method of measurement of optical cable stiffness at low temperatures

Abstract: In this article the new method of determination of optical cable stiffness at low temperatures is offered. The method is allows to simplify process of measurements. Thus presence of technicians at climatic chamber in the course of measurements is not required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The lifetime of the optical fibers is determined by stress corrosion process and depends from the mechanical stress in the optical fiber [1][2][3][4][5][6][7] . Researches of deformations of optical cables at the low temperatures showed that residual radial deformations of optical cables loose tubes can be the cause [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . Such deformations can be the cause of optical fibers stress at low negative temperatures and the cause of optical cables reliability decrease at fiber optical communication lines maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime of the optical fibers is determined by stress corrosion process and depends from the mechanical stress in the optical fiber [1][2][3][4][5][6][7] . Researches of deformations of optical cables at the low temperatures showed that residual radial deformations of optical cables loose tubes can be the cause [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . Such deformations can be the cause of optical fibers stress at low negative temperatures and the cause of optical cables reliability decrease at fiber optical communication lines maintenance.…”
Section: Introductionmentioning
confidence: 99%